Modernity without prejudice. Religion in American public life (v.3) (Journal of the Sociology and Theory of Religion, 2018)
The trilogy La Modernidad without prejudice is reviewed here. Religion in American public life, by Dr. Antonio Sánchez-Bayón, specialist in Political-Legal History and Philosophy, as well as Law and Comparative Politics. Although separated in three volumes, these three monographs (one of cultural foundations, another of normative politico-legal and the last on discourses) actually correspond to a single work, complete and round (on the influence of religion in public life American and its idiosyncratic development as a people).